Biodiversity and culture of prokaryotes inhabiting haloalkaline and meromictic Soap Lake, Washington, USA - Vanderlaan, Olivia J. M.; Simmons, Emily M.; Damman, Kelli M.; Waddell, Makenna D.; Ross, Savannah F.; Armstrong, Amanda D.; Walker, Mackenzie L.; Sattley, S. Josiah; Sattley, W. Matthew (Frontiers in Microbiology, 2025)
Despite their potential for harboring novel microorganisms exhibiting beneficial metabolisms or that produce useful products for biotechnology and industry, alkaline lakes and soils are among the least studied extreme environments. With its high productivity and meromictic water column, haloalkaline Soap Lake (Washington, USA) is among the most intriguing soda lakes in the world. We sampled the water column of Soap Lake and used both culture-based and culture-independent (16S rRNA amplicon-based) methods to analyze the microbial diversity of both its oxic and anoxic waters. Cultivable aerobic heterotrophs were specifically targeted in enrichment cultures, and over 100 isolates were obtained. Small-subunit rRNA gene sequences were obtained for isolates that exhibited diverse colony morphologies and grew well on alkaline media containing varying concentrations of NaCl, and two of these isolates were chosen for in-depth characterization: strain 12SL-E129, which aligned within the genus Roseinatronobacter; and strain SL14, of the genus Vibrio. Both strains grew optimally at or above pH 9 and were halophilic—no growth was evident in the absence of NaCl for either isolate. In addition, strain SL14 exhibited impressive cold adaptation, showing a faster growth rate at 0°C than at 37°C. Community (16S rRNA) analyses conducted on Soap Lake water samples from both the mixolimnion (3 m) and the monimolimnion (23 m) revealed an extensive diversity of Bacteria, with the shallower depth dominated by species of Pseudomonadota (especially Alphaproteobacteria), Actinomycetota, and Bacteroidota; Deep anoxic waters were dominated by Bacillota, including many taxa containing endospore formers, as well as a marked increase in sulfate-reducing Deltaproteobacteria. Only low numbers of Archaea were identified in both the upper and lower waters of Soap Lake. Our data suggest that despite its extreme conditions (high alkalinity, steep salinity gradient, and reportedly extraordinarily high sulfide concentrations in the monimolimnion), Soap Lake is a highly productive aquatic system supporting thriving and diverse bacterial communities.